2019
DOI: 10.1210/jc.2019-00166
|View full text |Cite
|
Sign up to set email alerts
|

Use of Glucose, Glutamine, and Fatty Acids for Trophoblast Respiration in Lean Women, Women With Obesity, and Women With Gestational Diabetes

Abstract: Objective Maternal obesity and gestational diabetes mellitus (GDM) are associated with adverse outcomes, particularly with a male fetus. The composition and amount of substrate supplied to the placenta are altered in these conditions. We hypothesized that there are sexually dimorphic differences in utilization of glucose, fatty acids, and glutamine between trophoblast of lean women, women with obesity, and women with GDM. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 46 publications
1
31
1
Order By: Relevance
“…Our control group consisted of placentas from non‐obese individuals without GDM, which decreases the potential confounding effect of the relative hyperglycemia observed in obese compared to normal weight pregnant persons 12,47 . Prior studies have demonstrated trophoblast metabolism is affected by GDM independent of obesity 15 . We appreciate that sex is a biologic variable that may affect CTB function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our control group consisted of placentas from non‐obese individuals without GDM, which decreases the potential confounding effect of the relative hyperglycemia observed in obese compared to normal weight pregnant persons 12,47 . Prior studies have demonstrated trophoblast metabolism is affected by GDM independent of obesity 15 . We appreciate that sex is a biologic variable that may affect CTB function.…”
Section: Discussionmentioning
confidence: 99%
“…Placental oxygen consumption supports ATP production required for protein synthesis, steroid hormone production, and nutrient transport systems by trophoblast cells. Placentas from pregnant persons with GDM exhibit compromised metabolism and lower rates of oxygen consumption 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…This ability to switch metabolite substrates depending on nutrient availability is called metabolic flexibility and is a crucial cell survival mechanism when faced with sub-optimal metabolic conditions. We recently showed that in addition to glucose, trophoblast cells can also utilize amino acids, e.g., glutamine, and fatty acids for generation of ATP via the ETC and that the proportions of each used can change with metabolic condition, e.g., obesity or gestational diabetes [ 6 ]. Since, the proliferative CT and differentiated ST have different role in terms of transport, metabolism, and steroid and peptide hormone production, we hypothesized that they might differ in their use of fuel sources and metabolic flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…This may be linked to the different fetal growth and survival strategies where male fetuses grow larger than female fetuses but are therefore at a greater risk of suffering from adverse pregnancy outcomes if maternal nutrition and placental function are not optimal [ 15 , 16 , 17 ]. We have previously reported maternal obesity, preeclampsia, and gestational diabetes mellitus to be associated with sexually dimorphic effects on energetics and autophagy in the placenta, and have also shown sexual dimorphism in placental antioxidant enzyme activity [ 6 , 18 , 19 , 20 ]. In this study we also investigated if fetal sex had effects on glycolytic and mitochondrial metabolism in CT vs. ST cells from women of a healthy weight.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reason for this sex disparity remains mysterious to date. In addition to obvious sex differences in nutrition, growth, and metabolism in preterm infants( 34 ), the placenta – transitory but critical fetal tissues to nurturing fetal development and growth – demonstrates sex dimorphism in many aspects including global gene expression( 35 ), steroid hormone production( 36 ), antioxidant buffering capacity ( 37 ), mitochondrial macronutrient metabolism( 38 ), responses to adverse maternal milieu such as obesity, inflammation, hypoxia, GDM, preeclampsia, and other pregnancy related disorders( 39 , 40 ). In the present study, we tried to associate the alteration of placental gene expression with macrosomia bias in males and found that increased expression of FABP4 is coincident with the higher incidence of macrosomia in male fetuses ( Fig.…”
Section: Discussionmentioning
confidence: 99%